Determination of polyphenol compounds in medicinal plants of local habitat and their importance for health (Environment & Health, 2022)
Objective: Assess the possibility of using some medicinal plants containing polyphenolic compounds (tannins and gallic acid) in medicine.Materials and methods: The Folin-Ciocalteu reagent spectrophotometry method is used to determine the amount of polyphenolic compounds. The gallic acid solution was selected as the standard sample. The objects of the study were dry specimens of plants: Oak Bark (quercus cortex), Rhizomes of Bistorta officinalis (bistortae rhizomata), Galls of Oak leaves (gallae turcicae), Rhizomes of Potentilla erecta (tormentillae rhizomata). Experimental samples in the form of aqueous and alcoholic extracts are made from this dry raw material.Results: Studies have shown that all selected plants have sufficient tannin content to confirm their healing properties. The largest number was found in the galls of oak leaves. Alcohol extracts extracted polyphenolic compounds from plant raw materials better than aqueous ones, but the difference is relatively small. Therefore, aqueous extracts can be used as therapeutic drugs for those who are contraindicated alcohol extracts.Conclusions: The studied dry specimens of plants (oak bark (quercus cortex), rhizomes of snake mustard (bistortae rhizomata), galls of oak leaves (gallae turcicae), rhizomes of erect cinquefoil (tormentillae rhizomata)) contain polyphenolic compounds (tannin and gallic acid) in sufficient quantities to provide medicinal effect. It has been shown that the extraction of polyphenolic compounds from plant materials using alcohol solutions is more efficient than aqueous extracts. It is recommended to use herbal products with tannins in medicinal practice.
Keywords: polyphenolic compounds; spectrophotometry; Folin–Ciocalteu method; extraction; tannins